Update on Opioid Addiction for Perioperative and Critical Unit Care: Anaesthesiologists Perspective - Rakesh Garg; Uma Hariharan (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2015)
Drug addiction remains a challenge in perioperative management for a surgical procedure for anaesthesiologists. Anesthesiologists are increasingly encountering patients with current or previous history of drug abuse in their day-to-day practice, both in the ED (emergency department) or ICU (intensive care unit) and the OR (operating room) [1]. The understanding of such addiction is important not only for patients safer outcome but also better perioperative pain management. Hence, anesthesiologists need to be aware of the possibility of drug abuse and its adverse effects on various body systems and be adequately trained to effectively manage the crucial perioperative period. Greater precautions need to be taken in patients with multiple or combination drug addiction, as opioids are commonly abused with tobacco, alcohol, cocaine and marijuana.